Newfoundland and Labrador on a Plate: Bed, Breakfast, and Regional Identity - Everett, Holly (Cuizine, 2011)
Culinary tourism is often a process of negotiation. This article explores the links between food production, place, and identity in the operation of bed and breakfasts (B&Bs) on Newfoundland’s west coast and the Labrador Straits. This area encompasses one of Newfoundland and Labrador’s major attractions, the Viking Trail. Due to the large number of tourists coming through and the relatively few restaurants in this area, some B&Bs offer evening meals as well as breakfast. Many offer local specialties, and almost all emphasize “home cooking.” Conversations around the dining table often concern the province and its culture, and provide B&B owners with an opportunity to perform local identities for their guests. Such presentations of self and place range from assertive refutations of the “Newfie” stereotype to semi-formal instruction. Proprietors may further frame the social aspects of the meal, and thus the performance as a whole, by assigning seating or moving guests through different spaces as the meal progresses. Through participant-observation and interviews with proprietors, this article concludes that these relatively informal social situations may facilitate significant intra- and intercultural exchanges. They enable communication that supports, personalizes, disrupts, and deconstructs both esoteric and exoteric grand narratives by utilizing a variety of strategies. These competing identities are shaped and maintained through formal and informal metaculinary discourse.